BAHASA DEMOKRATIS DI DALAM MEDIA TELEVISI INDONESIA - Santosa, Riyadi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
This research attempts to depicts the language used in Indonesian television, especially in news, editorial, and talk show in post reform era. The main issue in this research is the language used in Indonesian television contributes to the formation of democracy in this country. To answer the question, this research applies Systemic Functional Linguistics (SFL) that is able to portray the social processes and the language that is representation of the social processes, including their genres and registers. The results show that news exploits recount whereas editorial and talk show employ discussion genre. The recount and discussion genres in news and editorial and talk show accelerate the atmosphere of democratization in Indonesia. News provides facts and phenomena whereas editorial and talk show discusses them.Â  However, in the level of register, editorial and talk show exploit the use of more raised evaluation that a number of communication experts believe that Indonesian editorial and talk show go beyond the democracy level or are still provocative.Keywords: Bahasa Demokratis, Genre, Register, Appraisal